FEMALE ENTREPRENEURSHIP: CHARACTERISTICS AND MANAGEMENT PROFILE IN SMALL AND MEDIUM-SIZED ENTERPRISES - Martins, Cibele Barsalini; Crnkovic, Luciana Helena; Pizzinatto, Nadia Kassouf; Maccari, Emerson Antonio (Revista de Administração da UFSM, 2010)
The growing participation of women in the entrepreneurship area enables envision a future in which both genders will act in this area in a equilibrium state. The realization of this possibility, considering the Brazilian economy scenario for the coming years, represents more than a particularly optimistic view, but a necessary event in the view of the growth requirement in the Brazilian economy. In this article have been twofold: firstly, to know the entrepreneur’s personal characteristics related to their origin, educational history, professional experience and personal life and secondly, the identification of parameters that describes the role of entrepreneurship women in small and medium enterprises. The working method was based on an exploratorydescriptive approach and multi-case studies and data analysis used the Big Five Personality Model methodology. During the research it became evident that the obstacles are many and seemingly insoluble. However, all the entrepreneurs interviewed showed a mark in common: determination to pursue goals, achieving goals and overcoming difficulties, but it is undeniable that the private life of the entrepreneurs was affected differently.